Karolina Shiino as an arena of exclusion and negotiation of the Japanese national identity - Paramita Winny Hapsari (Universitas Dian Nuswantoro, 2026)
This study examines exclusionary discourses, panoptic aesthetics, and the construction of national identity in the controversy surrounding Karolina Shiino’s victory at Miss Japan 2024. Drawing on Foucault’s concepts of power/knowledge and the surveillance of the body, this study analyzes 59 Twitter posts and seven news articles from both national and international media. A critical discourse analysis approach was employed to identify narrative patterns, mechanisms of social surveillance, and the limits of inclusivity in representations of “Japaneseness.” The findings reveal that social media discourse was largely dominated by Japanese users questioning Shiino’s authenticity as a national representative, while mainstream media demonstrated varied stances. Some reinforced blood-based nationalism, while others opened discursive space for alternative perspectives. This dynamic illustrates how women’s bodies in beauty pageants become contested symbolic sites for negotiating national identity. The study highlights the need to understand the interplay between social and institutional media in shaping national narratives.